Growth and Structural Change in China-U.S. Trade - Hong Wang (Levy Economics Institute of Bard College, 1992)
Since the resumption of China-U.S. trade in 1972, and in particular since the establishment of diplomatic relations in early 1979, trade between the two countries has increased dramatically. By 1990, the United States was China's third-largest trading partner, accounting for 10.2% of China's total trade, 12.4% of Chinese imports, and 10.1% of total foreign investment. China's foreign exchange holdings had grown to 40 billion (sixth largest in the world), and its foreign borrowing to 53 billion. This represents an integration into the world economy believed impossible by most observers a decade earlier. A key to this success has been the decentralization reform of foreign trade structures undertaken by the Chinese leadership, and the adoption of the devaluation policy aimed at emulating the trade and economic growth strategies of Taiwan and South Korea. During the period examined, Hong Kong has played a crucial role in stimulating and facilitating trade between the two countries, and has provided experience in foreign trade operations to novice Chinese exporters. Furthermore, the British colony has aaed as a middleman-lowering transaction and transportation costs-for U.S. businesses wishing to trade with the rapidly growing number of Chinese foreign trade corporations. It is noted that the discrepancy in U.S. and Chinese government trade estimates results largely from the export of substantial Chinese goods to the U.S. through Hong Kong: Washington, unlike Beijing, counts these as Chinese goods. During this period, the slow growth in world trade has proved no constraint on the rapid growth in China-U.S. trade, and shows no signs of doing so. This is, in large part, due to the complementary nature of the two economies: Beijing sees the U.S. as a critical source of advanced technology and equipment to meet its modernization goals, while Washington regards China as a vast untapped marker for exports. The governments of the two countries have played a positive role in encouraging trade growth to date, and Wang points to the potentially disastrous consequences of revoking most-favored-nation trading status. The reduction in Chinese exports would, in turn, cause a loss of the foreign exchange needed to afford U.S. imports, and thus would have a negative effect on an already ailing U.S. domestic economy. The larger effects, particularly the "body blow" to Hong Kong, would reach far beyond the economic relations between the two countries.
Keywords: 330